RANCANGAN PROGRAM SISTEM INFORMASI CARGO BERBASIS WEB (STUDI KASUS: PT ALMANA KARTIKA UTAMA JAKARTA) - Muhammad Karim Amrullah; Eka Rini Yulia (Jurnal Mantik Penusa, 2019)
economy. This expedition service plays an important role in distribution and transportation to facilitate the flow of goods delivery. Forwarding companies must have advantages in logistics and distribution of goods, such as speed and accuracy in the delivery of goods. At this time PT Almana Kartika Utama Jakarta does not have a good shipping data recording and processing system and does not yet have an information system to customers, so customers have to ask manually to find out the status of his belongings, this is considered to be very inefficient and ineffective so it makes information to customers very slow. Therefore, researchers need to build a program design for a web-based cargo information system, to get the best solution in solving the problem, so that effective and efficient shipping of goods is achieved at PT. Almana Kartika Utama.